2011
DOI: 10.1603/me10197
|View full text |Cite
|
Sign up to set email alerts
|

Entomological Study on Transmission of Avian Malaria Parasites in a Zoological Garden in Japan: Bloodmeal Identification and Detection of Avian Malaria Parasite DNA From Blood-Fed Mosquitoes

Abstract: Several species of captive and wild birds have been found to be infected with various avian blood protozoa in Japan. We investigated the prevalence and transmission of avian malaria parasite and determined the bloodmeal hosts of mosquitoes collected in a zoological garden in Tokyo, Japan, by using the polymerase chain reaction. In total, 310 unfed and 140 blood-fed mosquitoes of seven species were collected by using sweep nets and CDC traps. Bloodmeal identification indicated that mosquitoes had fed on 17 avia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
50
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 28 publications
8
50
0
1
Order By: Relevance
“…Indeed, there already is a considerable record of zoofocused mosquito study (e.g. Beier & Trpis,1981;Nolen, 2001; Derraik, 2004a,b;McGowan, 2004;Sano et al, 2005;Nelder, 2007;Adler et al, 2011;Ejiri et al, 2011;Tuten, 2011a;Tuten 2011b;Tuten et al, 2012). However, the potential of national, regional and global-level zoo networks to contribute to mosquito-monitoring efforts remains largely unutilized.…”
Section: Survelliance Potential Of Zoo and Wildlife-park Networkmentioning
confidence: 99%
“…Indeed, there already is a considerable record of zoofocused mosquito study (e.g. Beier & Trpis,1981;Nolen, 2001; Derraik, 2004a,b;McGowan, 2004;Sano et al, 2005;Nelder, 2007;Adler et al, 2011;Ejiri et al, 2011;Tuten, 2011a;Tuten 2011b;Tuten et al, 2012). However, the potential of national, regional and global-level zoo networks to contribute to mosquito-monitoring efforts remains largely unutilized.…”
Section: Survelliance Potential Of Zoo and Wildlife-park Networkmentioning
confidence: 99%
“…, Yukita SATO 1) *, Kyeong-Soon KIM 2) , Mikako TAMASHIRO 3) , Yoshio TSUDA 2) , Takako TOMA 3) , Ichiro MIYAGI 3) , Koichi MURATA 4) and Masayoshi YUKAWA 4) Avian Plasmodium spp. are blood protozoa that cause the vector-borne disease of bird malaria on a worldwide scale and are transmitted mainly by mosquitoes of the genera Aedes, Anopheles, Culex and Culiseta [20].…”
mentioning
confidence: 99%
“…are blood protozoa that cause the vector-borne disease of bird malaria on a worldwide scale and are transmitted mainly by mosquitoes of the genera Aedes, Anopheles, Culex and Culiseta [20]. Previous studies in Japan reported that several species of wild and captive birds were infected with various strains of avian Plasmodium [10][11][12], and some mosquito species were reported as their vectors [2][3][4][5][6][7]. Elucidating the prevalence and transmission pathways of avian Plasmodium may provide important information for evaluating the risk of parasite infections in the study areas [3,4].…”
mentioning
confidence: 99%
See 2 more Smart Citations